Age of onset and the subclassification of conduct/dissocial disorder. (31st October 2014) - Silberg, Judy; Moore, Ashlee A.; Rutter, Michael
<x xml:space="preserve">Abstract</x> Background Conduct Disorder (CD) is a markedly heterogeneous psychiatric condition. Moffitt (1993) proposed that subclassification of CD should be according to age of onset. Our goals were to compare childhood‐onset and adolescent‐onset CD in terms of differences in phenotypic risk factors, genetic analyses, and factors associated with the persistence of antisocial behavior into young adulthood. Methods The data are from the Virginia Twin Study of Adolescent Behavioral Development (VTSABD) and Young Adult Follow‐Up (YAFU). Childhood‐onset CD was defined as CD beginning at or before age 11. Adolescent‐onset CD was defined as having CD onset between ages 14 and 17. These subgroups were compared on ADHD, young adult antisocial behavior (ASB), family dysfunction, and parental depression. Genetic analyses compare childhood‐onset and adolescent‐onset CD, as well as their cooccurrence with ADHD and ASB. Finally, predictors of persistence were examined. Results Childhood‐onset CD was significantly associated with ADHD, ASB, family dysfunction, and parental depression. Adolescent‐onset CD was marginally associated with parental depression (p = .05) but not with any of the other risk factors. Univariate genetic models showed that both childhood‐onset and adolescent‐onset CD involve a large genetic liability accounting for 62% and 65% of the variance, respectively. A common genetic factor (as well as an ADHD‐specific factor) accounted for the cooccurrence of childhood‐onset CD and ADHD. The cooccurrence of childhood‐onset CD and ASB are reflected by a common genetic factor with genetic specific effects on ASB. There was no etiological link between adolescent‐onset CD and either ADHD or ASB. Both ADHD and family dysfunction were significantly associated with the persistence of antisocial behavior into young adulthood. Conclusions Phenotypic findings differentiated between childhood‐onset and adolescent‐onset CD. ADHD and family dysfunction predicted persistence of antisocial behavior into young adulthood.